Transport vs. Metabolism: What Determines the Pharmacokinetics and Pharmacodynamics of Drugs? Insights From the Extended Clearance Model. Issue 5 (27th August 2016) - Patilea‐Vrana, G; Unadkat, JD
Abstract : The well‐stirred hepatic clearance model (WSHM) has been expanded to include drug transporters (i.e., extended clearance model [ECM]). However, the consequences of this expansion in understanding when transporters vs. metabolic enzymes will affect the pharmacokinetic (PK) and pharmacodynamic (PD) of drugs remains opaque. Identifying the rate‐determining step(s) in systemic or tissue drug PK/PD will allow accurate predictions of drug PK/PD and drug‐drug interactions (DDIs). Here, we clarify the implications of the ECM on PK/PD of drugs.